Implementasi Kebijakan Penghapusan Sanksi Administrasi Pajak Kendaraan Bermotor pada Kantor Samsat Cibinong Bogor Tahun 2022 - Salfarilla, Salsa Elsi; Selvi, Selvi (Jurnal Ilmu Administrasi Publik, 2024)
The problem faced by the West Java Province government, especially Cibinong Bogor One-stop Administration Services Office/Samsat in collecting vehicle tax, is that not all taxpayers are compliant in carrying out their tax obligations. To increase the PKB revenue target and increase the obligation to pay taxes, the government has imposed administrative sanctions on taxpayers who delay paying their taxes. Apart from providing administrative sanctions, the government also issued a policy regarding the elimination of administrative sanctions for vehicle Tax to relieve taxpayers. This research aims to find out the form of implementation of the policy of eliminating administrative sanctions for motor vehicle tax at One-stop Administration Services Office/Samsat Cibinong Bogor. This research uses descriptive qualitative research methods. Data collection in this research used interview, observation and documentation techniques. The results of this research show that the implementation of the policy of eliminating administrative sanctions for motor vehicle tax at the Cibinong Bogor One-stop Administration Services Office/Samsat has not gone well, the frequency of dissemination of information related to this policy has not been evenly distributed, the implementation of direct education and outreach by policy implementers to taxpayers has also not been optimal, there is a lack of consistency in the dissemination of information via social media, as well as miscommunication between policy implementers and taxpayers. This has resulted in many people still not knowing about the implementation of the policy of eliminating administrative sanctions for vehicle tax at the Cibinong Bogor One-stop Administration Services Office/Samsat. Apart from that, taxpayers also do not understand the concept of eliminating administrative sanctions for vehicle tax itself